Composite material carrying Au nanoclusters and method for producing said composite material

JP7642162B2Active Publication Date: 2025-03-07TANAKA KIKINZOKU KOGYO KK
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024535122
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-07-22
Filing Date
2023-07-20
Publication Date
2025-03-07
Estimated Expiration
2043-07-20

AI Technical Summary

Benefits of technology

【0049】 以上説明したように、本発明に係る複合材料は、疎水性担体にAuナノクラスターが担持された複合材料である。本発明に係る複合材料は、微細なAuナノクラスターが高密度で担持されており、Auナノクラスターが有する特異な特性を効果的に発揮することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007642162000004
    Figure 0007642162000004
  • Figure 0007642162000005
    Figure 0007642162000005
  • Figure 0007642162000006
    Figure 0007642162000006
Patent Text Reader

Abstract

The present invention relates to a composite material formed by carrying Au nanoclusters, each containing two or more Au atoms, on carriers via ligands. In the present invention, hydrophobic bodies, such as carbon powder, are employed as the carriers and an L-cysteine or an L-cysteine derivative that has a nonpolar residue is employed as the ligands. Also, the present invention discloses a method for effectively carrying the Au nanoclusters on hydrophobic carriers. With the present invention, as a result of reacting an Au source and the L-cysteine or the like, serving as the ligands, in a state in which the hydrophobic carriers are dispersed in an aqueous solvent, Au nanocluster synthesis and carrying thereof on the hydrophobic carriers simultaneously proceed. With the present invention, it is possible to manufacture a composite material in which Au nanoclusters are carried on hydrophobic carriers in a highly dispersed manner.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composite material in which Au nanoclusters are supported on a suitable carrier. More specifically, the present invention relates to a composite material in which nano-order Au nanoclusters are supported on a hydrophobic carrier via a specific ligand. Furthermore, the present invention relates to a method for producing a composite material capable of supporting Au nanoclusters in a highly dispersed state on a hydrophobic carrier in an aqueous solution system. [Background technology]

[0002] Metals, when finely divided into nano-sized particles, exhibit various properties not found in bulk, such as photoresponse properties (photoluminescence properties), fluorescence properties, light scattering and reflection properties, etc. For this reason, metal nanoparticles are being considered for application in various fields, such as light-emitting elements and fluorescent materials used in display devices, and electrode and wiring materials for various electronic and semiconductor devices.

[0003] In addition to the above-mentioned applications of electrical and optical device-related materials, metal nanoparticles are also extremely effective as catalysts for various chemical reactions. Since fine metal particles increase the metal surface area, their catalytic activity is greatly improved by miniaturizing them to the nano-order. Metal particles that have been miniaturized to the nano-order are called metal nanoclusters. There is no definitive definition of what a nanocluster is, but it is usually a collection of several to several hundred metal atoms.

[0004] Metal nanoclusters are often synthesized by a wet method (liquid phase), and are generally used in the form of a dispersion liquid in which metal nanoclusters are dispersed in a solvent. A common method for synthesizing metal nanoclusters is to add a reducing agent and a ligand (organic ligand) to a metal salt solution. In this synthesis method, the ligand bonds to multiple metal atoms generated by reduction, forming particles in which the metal atoms are clustered. The ligand is sometimes called a protective agent or dispersant, and has the effect of suppressing the aggregation of clustered metal nanoparticles and maintaining the dispersed state. In addition, the metal nanoclusters are used in the form of a dispersion liquid in which the metal nanoclusters are dispersed, which is applied to a support such as a catalyst, and the metal nanoclusters are adsorbed and fixed to the support.

[0005] The present invention relates to the application of nanoclusters composed of Au (gold) among metal nanoclusters. In addition to the above-mentioned characteristics, precious metals such as Au and Ag are metals that significantly express localized surface plasmon resonance (SPR). Au is a chemically stable metal and has favorable electrical properties. Furthermore, while Au does not exhibit catalytic activity in a bulk state, nano-order Au has catalytic activity in various chemical reactions such as the oxidation reaction of carbon monoxide. For these reasons, Au nanoclusters are expected to be a precursor material that can contribute to improving performance in the various applications mentioned above.

[0006] Known Au nanoclusters include those in which Au atoms are clustered using phosphine or thiol-based organic ligands (thiolates) as ligands. In particular, Au nanoclusters using glutathione (GSH), a thiolate, as a ligand are known to be highly stable due to the strong Au-S bond, as well as to be hydrophilic and stably dispersed in aqueous solvents. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2019-513184 A [Patent Document 2] JP 2007-45791 A [Non-patent literature]

[0008] [Non-Patent Document 1] Alaaldin M.Alkilany et.al.”Facile Hydrophobication of Glutathione-Protected Gold Nanoclustersand Encapsulation into Poly(lactide-co-glycolide) Nanocarriers”, scientific reports, https: / / www.nature.com / articles / s41598-019-47543-4 [Non-Patent Document 2] Site Li et. Al. “Monopalladium Substitution in Gold Nanoclusters Enhances CO2. ElectroreductionActivity and Selectivity”, ACS Catal.2020,10,12011-12016. Summary of the Invention [Problem to be solved by the invention]

[0009] As mentioned above, metal nanoclusters are generally used by adsorbing and supporting the metal nanoclusters dispersed in a solvent onto a support. In this case, in order to manufacture highly active catalysts or high performance devices, it is necessary to efficiently transfer and support the metal nanoclusters dispersed in the solvent onto a support. The same is true for Au nanoclusters, so it is necessary to support the dispersion of Au nanoclusters synthesized by the conventional method described above onto a support.

[0010] However, according to the investigations of the present inventors, conventional Au nanocluster dispersions may not be able to support some types of supports with sufficient efficiency. For example, when a dispersion of Au nanoclusters with glutathione as a ligand is supported on carbon powder, which is often used as a catalyst support, most of the Au nanoclusters may not be adsorbed onto the support and may remain in the solvent.

[0011] Considering the cause, it is thought to be due to the difference in polarity (hydrophilicity and hydrophobicity) between the Au nanoclusters and the carrier. To explain using the above example, Au nanoclusters with glutathione as a ligand are hydrophilic and stable in aqueous solvents, so adsorption and support onto hydrophobic carbon powder is difficult to proceed. As a result, most of the Au nanoclusters remain in the solvent without being supported by the hydrophobic carrier. Many catalyst carriers and device substrates have hydrophobic surfaces. Even if Au nanoclusters can stably maintain the nanoparticle state in a solvent, their significance is diminished if they cannot be supported by these carriers.

[0012] If the cause of the difficulty in loading is the hydrophobicity of the support, one solution is to use Au nanoclusters that can be dispersed in non-aqueous solvents such as organic solvents. In fact, Au nanoclusters that can exist stably in organic solvents are also known. For example, it has been reported that Au nanoclusters with phenylethanethiol as a ligand, as described in Non-Patent Document 2, are stable in the form of nanoparticles of about 1 nm in organic solvents. However, in order to apply the loading process using organic solvents to the manufacturing site of catalysts, etc., it is necessary to consider the environmental load caused by management of the working environment during use and waste liquid treatment, and measures to address this are not easy.

[0013] Thus, although there are many studies on Au nanoclusters related to their synthesis, there are few studies that consider the process of supporting the synthesized Au nanoclusters on a support. However, in order to apply Au nanoclusters to functional materials such as catalysts, it is also important to investigate efficient methods of supporting them.

[0014] The present invention was made under the above-mentioned background, and relates to a composite material in which Au nanoclusters, which are fine particles, are supported on a hydrophobic support in a highly dispersed state at an appropriate supporting density. The present invention aims to clarify a method for supporting Au nanoclusters on a hydrophobic support using an aqueous solvent, and to provide a method for producing the composite material. [Means for solving the problem]

[0015] In order to solve the above problems, the present inventors first investigated the behavior of Au clusters synthesized in aqueous solvents using various thiolate ligands including glutathione. As a result, they found that L-cysteine ​​and L-cysteine ​​derivatives having a specific residue can synthesize Au nanoclusters in aqueous solvents without the action of a reducing agent. They also confirmed that Au nanoclusters synthesized using these ligands have hydrophobicity. However, the fact that Au nanoclusters are hydrophobic means that it is difficult to stably disperse them in aqueous solvents. The Au nanoclusters using L-cysteine ​​and L-cysteine ​​derivatives investigated by the present inventors cause precipitation and deposition due to aggregation in the solvent after synthesis, and cannot maintain a stable dispersion state.

[0016] Even if Au nanoclusters have hydrophobicity in an aqueous solvent, if the dispersion state after synthesis is unstable, it is difficult to use this solution for supporting on a hydrophobic carrier. As a result of further investigation and consideration, the present inventors have found that if a hydrophobic carrier is present in an aqueous solvent at the time when the above-mentioned ligand reacts with the Au source (Au ions) to synthesize Au nanoclusters, the Au nanoclusters can be adsorbed and supported on the carrier at the same time as synthesis. This is thought to be because Au nanoclusters synthesized using L-cysteine ​​and L-cysteine ​​derivatives have good adsorption to hydrophobic carriers, and adsorption to the carrier takes precedence over the aggregation of the nanoclusters.

[0017] The inventors then investigated the structure and properties of a composite material in which Au nanoclusters are supported on a hydrophobic support simultaneously with synthesis as described above, and confirmed that in this composite material, Au nanoclusters are supported on the hydrophobic support at high density and high dispersion, leading to the invention.

[0018] In other words, the present invention is a composite material comprising an Au nanocluster containing two or more Au atoms supported on a support via a ligand, wherein at least the portion of the support where the Au nanocluster is supported is hydrophobic, and the ligand is L-cysteine ​​or an L-cysteine ​​derivative having a nonpolar residue.

[0019] The configuration of the composite material carrying Au nanoclusters according to the present invention and a method for producing the composite material based on a method for carrying Au nanoclusters on a hydrophobic carrier will be described below.

[0020] (A) Composite material carrying Au nanoclusters according to the present invention The composite material according to the present invention is composed of a support, Au nanoclusters supported on the support, and a ligand that bonds the two together.

[0021] (A-1) Hydrophobic carrier The carrier is a member for supporting the Au nanoclusters in a dispersed state. The carrier of the composite material according to the present invention is a carrier having hydrophobicity at least in the portion where the Au nanoclusters are supported. Hydrophobicity means a property of having low affinity for water and being difficult to dissolve or mix with water. Constituent materials of the carrier include carbon, cellulose, nitrocellulose, hydrophobic polymers (fluororesin, acrylic, epoxy, polyethylene, polystyrene, polyvinyl chloride, etc.), metal nitrides, etc. There are no particular limitations on the shape and dimensions of the carrier. Particulate carriers are often used in catalysts. In addition, bulk carriers such as plate-shaped, sheet-shaped, and film-shaped carriers may be used as carriers for material applications related to electrical and optical devices. In the present invention, specific standards for the hydrophobicity of the carrier can be set for each of particulate carriers and bulk carriers as follows.

[0022] (i) Particulate carrier The particulate carrier is a particulate or powdered solid having a particle size of 10 μm or less that can be dispersed in a solvent such as water. The R SP The hydrophobicity of a carrier dispersed in an aqueous solvent can be evaluated based on the magnitude of the interaction between the carrier surface and the solvent molecules. Pulsed NMR makes it possible to measure the relaxation time of a solvent that has protons (H) in its molecules, such as water, and the shorter this relaxation time, the stronger the interaction between the carrier and the solvent. In determining hydrophobicity using pulsed NMR, the relaxation times are measured in both the solvent alone and in the solvent with the particulate carrier dispersed therein, and R SP Find the value. R SP The value is calculated using the following formula: SP The smaller the value, the higher the hydrophobicity.

[0023]

number

[0024] The hydrophobicity of the carrier used in the present invention is determined by measuring the relaxation time (transverse relaxation time (spin-spin relaxation time)) by pulse NMR using water as the solvent, and calculating R SP The value is calculated and judged. SP The correction value (R SP / TSA:Hereafter, R SP(c) In the present invention, it is preferable to judge the hydrophobicity by R SP(c) A carrier having a value of 0.5 or less is considered to be a hydrophobic carrier. The total surface area (TSA) of a carrier during pulse NMR measurement can be calculated using the following formula.

[0025]

number

[0026] In the above formula, it is preferable to use the BET specific surface area as the specific surface area SA of the support. The present invention is assumed to be applied to catalysts, and carbon particles and the like are often used as catalyst supports. Carbon particles have various forms, such as a structure having countless fine pores on the surface and a hollow structure. It is preferable to use the BET specific surface area in determining the specific surface area of ​​these various forms of particulate supports. It is preferable to use a value measured by a gas adsorption method as the BET specific surface area, and it is preferable to use a value measured by nitrogen gas. In addition, it is preferable to use a mass-to-volume ratio concentration of the support during pulse NMR measurement of 0.1% or more (0.001 g / mL or more) and 10% or less (0.1 g / mL or less).

[0027] (ii) Bulk carrier The bulk carrier is intended to exclude the particulate carriers described above, and is a plate-like, block-like, or thin-film-like solid with a minimum size of 10 μm or more. The hydrophobicity of a bulk carrier can be determined by the contact angle with water. In the present invention, a carrier with a contact angle with water of 90° or more is considered to be hydrophobic. For a bulk carrier with a minimum size larger than that of a particulate carrier, at least the surface portion carrying the Au nanoclusters should have the above-mentioned hydrophobicity. Even if the material is a material other than the above-mentioned hydrophobic materials, it is sufficient that the surface carrying the Au nanoclusters is treated to give hydrophobicity. Examples of hydrophobic treatment include treatment to modify the carrier surface with nonpolar functional groups (alkyl groups, etc.), firing treatment under an inert atmosphere, and coating with the above-mentioned hydrophobic materials.

[0028] (A-2) Au nanocluster Au nanoclusters are particles containing a group of two or more Au atoms. The Au nanoclusters supported on the hydrophobic carrier in the composite material of the present invention preferably have a particle size of 0.5 nm to 5 nm, more preferably 3 nm or less. The particle size of the Au nanoclusters can be obtained by, for example, measuring the particle sizes of multiple particles based on an image observed by an electron microscope such as a TEM, and calculating the average value. The particle size in the observed image can be measured by image analysis in addition to visual inspection. The particle size distribution can also be analyzed by statistical calculation of the measured particle size. In addition, in terms of measuring the particle size distribution, it is preferable to arbitrarily select 100 or more particles and measure the particle size. In addition, the "particle size" means the maximum distance (circumscribed circle equivalent diameter) among the distances between any two points on the contour line of the particle.

[0029] The Au nanocluster may be composed of Au atoms only, but may also contain atoms of other elements. For example, atoms of elements that have a high bond with Au, such as S (sulfur), O (oxygen), N (nitrogen), C (carbon), Cu (copper), and Ag (silver), may contribute to the stability and high activity of the Au nanocluster. It is preferable that such atoms other than Au account for 50% or less of the total number of atoms.

[0030] The amount (loading density) of the Au nanoclusters supported in the present invention is adjusted depending on the application of the composite material. According to the supporting method according to the present invention described later, the amount of the Au nanoclusters supported can be 0.1 mass % or more and 50 mass % or less based on the mass of the entire composite material such as a catalyst.

[0031] (A-3) Ligands (L-cysteine ​​and L-cysteine ​​derivatives) The ligand is an organic ligand that coordinates with the Au atom to maintain the aggregated state of the Au atom cluster. In the present invention, the ligand also acts as an assistant for binding the Au nanocluster to the hydrophobic carrier when the Au nanocluster is synthesized. The ligand of the present invention is L-cysteine ​​and an L-cysteine ​​derivative represented by the following formula:

[0032] [ka]

[0033] In the above formula, R is a residue (substituent) and is hydrogen or a non-polar residue. According to the investigations by the present inventors, L-cysteine ​​in which R is hydrogen or an L-cysteine ​​derivative in which R is a non-polar residue confers hydrophobicity to the Au nanocluster when coordinated to an Au atom in an aqueous solvent to form a nanocluster.

[0034] When R in the above formula is a non-polar residue, the non-polar residue is preferably an acyl group having an aliphatic hydrocarbon chain having 1 to 4 carbon atoms (acetyl group (CHCO:Ac), ethylcarbonyl group (CHCHCO), linear or branched propylcarbonyl group (C3HCO), linear or branched butylcarbonyl group (C4HCO)) or an alkoxycarbonyl group having an aliphatic hydrocarbon chain having 1 to 4 carbon atoms (methoxycarbonyl group (CHOCO), ethoxycarbonyl group (CHCHOCO), linear or branched propoxycarbonyl group (CHOCO), linear or branched butoxycarbonyl group (C4HOCO)). Among these, acetyl group (CHCO:Ac), isopropylcarbonyl group ((CH)CHCO), and tert-butoxycarbonyl group ((CH)COCO) are more preferable.

[0035] In addition, when an L-cysteine ​​derivative having a non-polar residue is used as a ligand, the non-polar residue is considered to have an anchoring effect on the hydrophobic carrier and to have an effect of suppressing the movement of Au nanoclusters in a high-temperature environment, which suppresses the aggregation of Au nanoclusters and the resulting coarsening of particles.

[0036] Particularly preferred ligands are L-cysteine ​​where R is hydrogen and N-acetyl-L-cysteine ​​where R is an acetyl group, because they have small molecular weights and can be easily decomposed and removed by heat.

[0037] In the composite material according to the present invention, the content of the ligand is preferably 0.1% by mass or more and 50% by mass or less based on the mass of the entire composite material such as a catalyst, and more preferably 20% by mass or less.

[0038] The ligand only needs to be bonded to at least a part of the Au nanocluster, and does not need to be bonded to the entire surface or all of the Au atoms. In addition, in the composite material according to the present invention, the presence of the ligand L-cysteine ​​or an L-cysteine ​​derivative in which R is a non-polar residue can be qualitatively confirmed by gas chromatography mass spectrometry (GC / MS), particularly pyrolysis-gas chromatography mass spectrometry (Py-GC / MS). The non-polar residue of the L-cysteine ​​derivative can also be confirmed by this analysis method.

[0039] (B) Manufacturing method of the composite material according to the present invention (Method of supporting Au nanoclusters) Next, a method for producing a composite material carrying Au nanoclusters according to the present invention will be described. As described above, the present invention produces a composite material carrying Au nanoclusters by synthesizing hydrophobic Au nanoclusters using L-cysteine ​​or an L-cysteine ​​derivative having a specific residue as a ligand, and carrying the Au nanoclusters on a hydrophobic carrier at the same time as the synthesis. In order to simultaneously generate and carry out the synthesis and carrying of Au nanoclusters, it is necessary to make the carrier coexist in the aqueous solvent, which is the reaction system, at the time when the Au source, which is the starting point of the synthesis reaction, comes into contact with the ligand.

[0040] In other words, the method for producing a composite material carrying Au nanoclusters according to the present invention includes the steps of: creating a state in which an aqueous solvent containing either an Au source or a ligand is in contact with at least a portion of a carrier; and then adding the other of the Au source and the ligand to the aqueous solvent, thereby synthesizing Au nanoclusters in the aqueous solvent and carrying the Au nanoclusters on the carrier; wherein the ligand is L-cysteine ​​or an L-cysteine ​​derivative having a nonpolar residue.

[0041] Previous studies on metal nanoclusters (Au nanoclusters) have focused on the synthesis of Au nanoclusters, and the support on the support is premised on the completion of the synthesis of Au nanoclusters. In contrast, in the present invention, the support on the support is completed simultaneously with the synthesis of Au nanoclusters, or instantaneously after the synthesis of Au nanoclusters. In the present invention, a reaction system in which either the Au source or the ligand coexists with the support is formed before the synthesis of Au nanoclusters, and the other of the Au source or the ligand is allowed to act on this reaction system to synthesize Au nanoclusters and support them on the support. The present invention differs from the prior art in the timing of the synthesis and support of Au nanoclusters. Below, a method for producing a composite material based on this method for supporting Au nanoclusters will be described.

[0042] In the present invention, it is necessary to first form a state in which the aqueous solvent containing either the Au source or the ligand is in contact with the carrier. In this step, the aqueous solvent may be in contact with the carrier, or a solution in which either the Au source or the ligand is added to the aqueous solvent may be prepared in advance, and the solution may be brought into contact with the carrier. The formation of the state in which the aqueous solvent or solution is in contact with the carrier is preferably performed by immersing a part or the whole of the carrier in the aqueous solvent or solution. This is because a sufficient amount of solvent is required to uniformly proceed with the Au nanocluster synthesis reaction that is initiated by adding the other of the Au source and the ligand thereafter. However, as long as a state in which the synthesis reaction of the Au nanoclusters can be caused can be maintained, the aqueous solvent or solution may be dropped or applied onto the carrier. The carrier is a hydrophobic carrier as described above.

[0043] The aqueous solvent may be pure water or a mixture of water and a water-soluble polar solvent (such as alcohol or N-methylpyrrolidone). The amount of the aqueous solvent is preferably 2 to 1000 times the weight of the carrier.

[0044] The Au source may be an Au salt such as tetrachloroaurate (III) acid, gold halide, or potassium gold (I) cyanide. The amount of the Au source added (Au concentration in the aqueous solvent) is related to the amount of Au nanoclusters supported on the support, so the concentration of the Au source should not be limited. For example, when considering catalytic applications, the Au source should be 0.1 mass% or more and 50 mass% or less of the support weight in terms of the mass of Au, so that the above-mentioned Au nanocluster support density can be obtained.

[0045] As described above, the ligand is L-cysteine ​​or an L-cysteine ​​derivative having a non-polar residue. The amount of the ligand to be added is preferably 1 to 10 times the moles of Au ions on a molar basis, taking into consideration the amount of Au nanoclusters to be supported. The ligand L-cysteine ​​etc. also acts as a reducing agent, and if the amount is less than 1, the Au ions may not be completely reduced. In addition, a lack of ligand also reduces the stability of the Au nanoclusters. On the other hand, if there is 10 times or more of the ligand, the Au atoms tend to be stabilized in a complex state in which the ligand is coordinated, and the synthesis efficiency of the nanoclusters decreases.

[0046] Then, the carrier is contacted with the aqueous solvent to which either the Au source or the ligand has been added, and then the other of the Au source and the ligand is added to synthesize the Au nanoclusters. At this time, L-cysteine ​​or an L-cysteine ​​derivative acts as a reducing agent in addition to its function as a ligand. Therefore, in the present invention, when the Au source and the ligand coexist in the reaction system without adding a reducing agent, the synthesis of the Au nanoclusters starts and proceeds at the same time. The synthesized Au nanoclusters are adsorbed and supported by the hydrophobic carrier. This support of the Au clusters proceeds instantaneously to an extent that cannot be distinguished by naked eye observation, either simultaneously with or after the synthesis of the Au clusters.

[0047] The temperature conditions of the reaction system in the synthesis and support of the above Au nanoclusters are preferably from 0° C. to 50° C., but may be room temperature. The reaction atmosphere may be either air or inert gas.

[0048] The synthesis of Au nanoclusters and their support on the hydrophobic support are completed, and a composite material can be obtained. The support on which the Au nanoclusters are supported may be recovered by drying or filtration, and may be washed, dried, or heat-treated as necessary. The heat treatment is performed to decompose and remove excess ligands and to associate the Au nanoclusters to control the particle size. The heat treatment atmosphere is preferably an air atmosphere or a mixed gas atmosphere of oxygen gas and an inert gas, as well as a reduced pressure atmosphere (preferably a reduced pressure atmosphere of 100 Pa or less) or an inert gas atmosphere. The heat treatment temperature is preferably 100°C or more and 800°C or less, more preferably 120°C or more and 400°C or less. Effect of the Invention

[0049] As described above, the composite material according to the present invention is a composite material in which Au nanoclusters are supported on a hydrophobic carrier. The composite material according to the present invention supports fine Au nanoclusters at a high density, and can effectively utilize the unique properties of the Au nanoclusters.

[0050] The present invention also elucidates a method for producing a composite material by efficiently supporting Au nanoclusters in an aqueous solvent. According to the present invention, a composite material can be produced by supporting Au nanoclusters on a hydrophobic support without relying on organic solvents, which are difficult to use from the viewpoint of environmental load, etc.

[0051] When Au is made into nanoclusters, it has catalytic activity that is not present in bulk. Au nanoclusters have catalytic activity for the oxidation reactions of carbon monoxide, alcohol, and styrene, and for the hydrogenation reactions of unsaturated ketones. The present invention can be applied as a catalyst for these chemical reactions. For example, carbon monoxide removal catalysts for generating reformed hydrogen gas and exhaust gas purification catalysts can be mentioned. In addition, Au nanoclusters have catalytic activity for the oxygen reduction reaction (ORR) as an electrode catalyst. The present invention can also be used as an electrode catalyst for fuel cells. [Brief description of the drawings]

[0052] [Figure 1] TEM images of the composite materials carrying Au nanoclusters in Examples 1 to 3. [Diagram 2] 1 shows MS spectra of the composite material carrying Au nanoclusters (Au(C) / C) of Example 1 before and after heat treatment. [Diagram 3] MS spectra of the composite material carrying Au nanoclusters (Au(NAC) / C) of Example 2 before and after heat treatment. [Figure 4] 1 shows MS spectra of the composite material carrying Au nanoclusters (Au(C) / C) of Example 3 before and after heat treatment. [Diagram 5] FIG. 1 is a comparison of MS spectra of the composite materials of Example 1 and Example 2 before and after heat treatment. [Figure 6] FIG. 1 is a comparison of MS spectra of the composite materials of Example 1 and Example 2 after heat treatment. [Figure 7] TEM images of the composite materials carrying Au nanoclusters of Examples 4 and 5. [Figure 8] TEM images of the composite materials carrying Au nanoclusters of Examples 6 and 7. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0053] First embodiment Hereinafter, an embodiment of the present invention will be described. In this embodiment, carbon powder was used as a hydrophobic carrier. In addition, L-cysteine ​​and N-acetyl-L-cysteine ​​(hereinafter referred to as acetylcysteine) were used as ligands for synthesizing Au nanoclusters to produce a composite material.

[0054] The carbon powder used in this embodiment has an average particle size of 40 nm and a BET specific surface area of ​​800 m 2 The carbon powder (0.1 g) was dispersed in 100 mL of pure water to prepare a slurry sample, which was analyzed by pulsed NMR. SP The measurements were performed using a pulsed NMR device manufactured by Resonance Systems, with a measurement sample volume of 1 mL, a measurement temperature of 30°C, a resonance frequency of approximately 20 MHz, and an observation nucleus of 1The relaxation time (transverse relaxation time T2) was measured by H-NMR (CMPG method).

[0055] R of the carbon powder of this embodiment to water SP The BET specific surface area (800 m 2 / g), the total surface area (TSA) of the support is 0.8 m 2 Therefore, the correction value R by TSA of the carbon powder of this embodiment is SP(c) was 0.35, and it was determined to be a hydrophobic carrier.

[0056] Example 1 (Ligand: L-cysteine ​​(C)) 1 g of the above carbon powder was added and dispersed in 100 mL of pure water as an aqueous solvent. 0.75 g (2.2 mmol of Au) of tetrachloroauric (III) acid was dissolved as an Au source in the aqueous solvent in which the carbon powder carrier was dispersed.

[0057] Then, 20 mL of an aqueous solution in which 1.2 g (9.3 mmol) of L-cysteine, a ligand, was added to the Au aqueous solution in which the carrier was dispersed, to synthesize Au nanoclusters, which were simultaneously supported on carbon powder to produce a composite material (Au(C) / C). The atmospheric temperature for the above operations was room temperature (25°C) in an air atmosphere.

[0058] After the Au nanoclusters were supported on the carbon powder, the reaction solution was filtered to recover the composite material and the filtrate. The recovered composite material was then subjected to two types of treatment: drying under reduced pressure (100 Pa or less) and then heating at 150°C for 4 hours under reduced pressure (100 Pa or less) to complete the composite material.

[0059] Example 2 (Ligand: Acetylcysteine ​​(NAC)) Carbon powder was dispersed in the same amount of pure water as in Example 1, 0.75 g (Au 2.2 mmol) of tetrachloroauric (III) acid, which is the Au source, was dissolved, and 20 mL of an aqueous solution in which 1.5 g (9.3 mmol) of acetylcysteine ​​was dissolved as a ligand was added to produce a composite material (Au(NAC) / C). The composite material was then collected in the same manner as in Example 1 and heat-treated at 150°C.

[0060] Example 3 (Ligand: L-cysteine ​​(C)) In this example, the order of addition of the Au source and the ligand was reversed from that of Example 1, and Au nanoclusters were synthesized and supported. Carbon powder was dispersed in the same amount of pure water as in Example 1, and 1.2 g (9.3 mmol) of L-cysteine ​​as a ligand was added, followed by the addition of 20 mL of an aqueous solution in which 0.75 g (2.2 mmol) of tetrachloroauric (III) acid as the Au source was dissolved, to produce a composite material (Au(C) / C). Thereafter, the composite material was collected in the same manner as in Example 1 and heat-treated at 150°C.

[0061] The Au nanocluster-supported composite materials produced in Examples 1 to 3 were observed with a STEM (JEM-ARM200F manufactured by JEOL Ltd.) immediately after production (before heat treatment) and after heat treatment. STEM images of each Example are shown in FIG. 1. In the state where Au nanoclusters are supported, fine Au nanoclusters of about 1 nm are supported in both Examples 1 and 2. When this is heat-treated at 150°C, slight aggregation occurs, resulting in Au nanoclusters of 1.0 nm (Example 1), 1.0 nm (Example 2), and 0.9 nm (Example 3). The particle size of these nanoclusters was calculated by fitting the scattering curve obtained when measuring with a small angle X-ray scattering device (NANOPIX manufactured by Rigaku Corporation) at a camera length of 600 mm.

[0062] Next, the composite materials of Examples 1 and 2 were analyzed by pyrolysis GC / MS to confirm the presence of ligands and to identify non-polar residues. Pyrolysis GC / MS was performed using an Agilent Technologies 7890A / 5975C instrument, in which components decomposed at a heating furnace temperature of 600°C were introduced into a GC for separation and analysis by MS. As analysis results, the MS spectra of the composite materials of Examples 1 to 3 before and after the heat treatment are shown in Figures 2 to 4. Also, the MS spectra of Examples 1 and 2, which have different ligands, are compared in Figures 5 and 6.

[0063] From Figures 2 to 4, a peak derived from L-cysteine ​​was detected in all of Examples 1 to 3, and the peak was detected even after heat treatment at 150°C, so the presence of the ligand L-cysteine ​​and L-cysteine ​​derivatives could be confirmed. In addition, although the order of mixing the Au source and the ligand is different in Examples 1 and 3, there is no difference in the spectra, so it is presumed that the structure of the Au nanocluster is the same depending on the order of mixing with the solvent and carrier. Furthermore, from Figures 5 and 6, peaks of acetic acid and acetamide derived from non-polar residues, which are the difference between the ligands in Examples 1 and 2, are observed, so the type of L-cysteine ​​derivative can also be identified.

[0064] Comparative Example Next, as a comparative example for confirming the supporting efficiency of Au nanoclusters in Examples 1 to 3, Au nanoclusters were synthesized and supported on carbon powder using glutathione as a ligand. In order to keep the conditions the same, in this comparative example, Au nanoclusters were synthesized and supported in a solvent in which the support is dispersed, as described below.

[0065] 20 mL of an aqueous solution in which 2.85 g (9.3 mol) of glutathione was dissolved in an aqueous solution in which 0.75 g (2.2 mmol) of tetrachloroauric acid was dissolved as an Au source was added to pure water in which the same amount of carbon powder as in Example 1 was dispersed. After the addition of glutathione, the composite material was collected and heat-treated at 150°C in the same manner as in Example 1.

[0066] [Investigation of Au nanocluster loading efficiency] After producing the Au nanocluster-supported composite material of the above comparative example, the amount of Au nanoclusters remaining in the reaction solution after supporting the Au nanoclusters was examined for Examples 1 to 3 and the comparative example. In this examination, the filtrate after recovering the composite material from the reaction solution after supporting the Au nanoclusters was analyzed by ICP-OES (ICP optical emission spectroscopy: ICPE-9820 manufactured by Shimadzu Corporation) to measure the amount of Au in the filtrate. Then, the ratio (%) of the amount of Au in the filtrate to the amount of Au added to the solvent before the synthesis of the Au nanoclusters was calculated.

[0067] From the results of this study, the ratio of Au in the filtrate was 0.03% in Example 1 (Au(C) / C), 0.015% in Example 2, and 0.075% in Example 3. From these results, it was confirmed that most of the charged amount of Au source was supported on the carrier as Au nanoclusters. On the other hand, the ratio of Au in the filtrate of the comparative example was 32.8%, which was clearly higher than those of Examples 1 to 3, and it was confirmed that a considerable amount of Au was not supported on the carrier. It can be seen that the Au nanoclusters synthesized by glutathione, which is the ligand of the comparative example, are water-soluble and difficult to support on the hydrophobic carbon powder carrier.

[0068] [Evaluation of catalytic activity] Next, the Au nanocluster-supported composite materials of Examples 1 to 3 were subjected to a catalytic activity evaluation test. In the activity evaluation test, 10 mg of the catalyst (composite material) of each Example and Comparative Example after heat treatment was collected, and 2 mL of tetramethylbenzidine solution (manufactured by SeraCare Life Sciences Inc. (KPL)) and 0.1 mL of 30% hydrogen peroxide solution were added to each, and the mixture was stirred at room temperature (25°C) for 1 minute. Then, 4 mL of 1 M hydrochloric acid was added as a reaction stop solution, and the reaction solution was passed through a 0.45 μm filter to remove the catalyst powder, and the absorbance at a wavelength of 452 nm was measured with an absorption spectrometer (V-770DS manufactured by JASCO Corporation). The catalytic reaction here is an oxidative decomposition reaction of hydrogen peroxide, and the catalytic activity is evaluated by the intensity of the absorbance of the resulting tetramethylbenzidine dimer.

[0069] The results of the evaluation test showed that the absorbance intensity was 2.26 for Example 1 (Au(C) / C), 1.97 for Example 2 (Au(NAC) / C), and 1.95 for Example 3 (Au(C) / C), confirming that each Example exhibited equivalent oxidation catalytic activity.

[0070] Second embodiment In this embodiment, the same carbon powder (average particle size: 40 nm, BET specific surface area: 800 m) as in the first embodiment is used as the hydrophobic carrier. 2 / g, R SP(c)0.35) was used, and acetylcysteine ​​(NAC) was used as a ligand for synthesizing Au nanoclusters, and a composite material was produced under production conditions different from those in the first embodiment.

[0071] Example 4 (Ligand: Acetylcysteine ​​(NAC)) 4 g of carbon powder was added and dispersed in 400 mL of pure water, which is an aqueous solvent. After adding 6 g (37.2 mmol) of acetylcysteine, which is a ligand, to the aqueous solvent in which the carbon powder carrier was dispersed, 20 mL of an aqueous solution in which 3 g (8.8 mmol) of tetrachloroauric acid, which is an Au source, was dissolved was added to produce a composite material (Au(NAC) / C). After that, in the same manner as in Example 1, the composite material was collected and dried, and then heated at 150°C under reduced pressure (100 Pa or less) for 4 hours to complete the composite material.

[0072] Example 5 (Ligand: Acetylcysteine ​​(NAC)) Under the same conditions as in Example 4, a ligand (NAC) was added to the aqueous solvent in which the carbon powder was dispersed, and then an aqueous solution of the Au source (tetrachloroauric acid (III)) was added to produce a composite material (Au(NAC) / C). The composite material was then collected and dried, and then heated at 400°C under reduced pressure (100 Pa or less) for 4 hours to complete the composite material.

[0073] The Au nanocluster-supported composite materials produced in Examples 4 and 5 were observed by TEM. TEM images of these composite materials are shown in Figure 7. As in the first embodiment, the particle size of the Au nanoclusters in these Au nanocluster-supported composite materials was measured by a small angle X-ray scattering device, and the results were 0.8 nm (Example 4) and 4.3 nm (Example 5). It was confirmed that the particle size of the Au nanoclusters could be changed by adjusting the heat treatment temperature.

[0074] Third embodiment In this embodiment, a carbon powder different from that in the first embodiment was used as a hydrophobic carrier, and L-cysteine ​​(C) was used as a ligand to produce a composite material.

[0075] The carbon powder used in this embodiment has an average particle size of 40 nm and a BET specific surface area of ​​220 m2 The carbon powder was dispersed in 100 mL of pure water to prepare a slurry sample, which was analyzed by pulsed NMR. SP The measurements were performed using a Bruker pulsed NMR device with a measurement sample volume of 2 mL, a measurement temperature of 30°C, a resonance frequency of approximately 20 MHz, and observation nuclei of 1 The relaxation time (transverse relaxation time T2) was measured using H-NMR. SP The value was 1.70. The total surface area (TSA) of the support was 4.4 m 2 Therefore, the R of the carbon powder of this embodiment SP(c) was 0.39, and it was determined to be a hydrophobic carrier.

[0076] Example 6 (Ligand: L-cysteine ​​(C)) 4 g of carbon powder was added and dispersed in 80 mL of pure water, which is an aqueous solvent. 4.8 g (37.2 mmol) of L-cysteine, which is a ligand, was added to the aqueous solvent in which this carbon powder carrier was dispersed, and then 20 mL of an aqueous solution in which 3 g (8.8 mmol) of tetrachloroauric (III) acid, which is an Au source, was dissolved was added to produce a composite material (Au(C) / C). Thereafter, in the same manner as in Example 1, the composite material was collected and dried, and then heated at 150°C under reduced pressure (100 Pa or less) for 4 hours to complete the composite material.

[0077] Example 7 (Ligand: L-cysteine ​​(C)) Under the same conditions as in Example 6, a composite material (Au(C) / C) was produced by adding a ligand (C) to an aqueous solvent in which carbon powder was dispersed, and then adding an aqueous solution of an Au source (tetrachloroauric acid (III)) to the aqueous solution. The composite material was then recovered and dried, and then heated at 230°C under reduced pressure (100 Pa or less) for 4 hours to complete the composite material.

[0078] The Au nanocluster-supported composite materials produced in Examples 6 and 7 were observed by TEM. TEM images of these composite materials are shown in FIG. 8. As in the first embodiment, the particle size of the Au nanoclusters in these Au nanocluster-supported composite materials was measured by a small-angle X-ray scattering device, and the results were 0.7 nm (Example 6) and 2.0 nm (Example 7). In this embodiment, a hydrophobic carrier different from that in the first embodiment was used, but it was confirmed that a composite material supported with fine Au nanoclusters could be produced as in the first embodiment. Also, in this embodiment, it was confirmed that the particle size of the Au nanoclusters could be changed by adjusting the heat treatment temperature. [Industrial Applicability]

[0079] As described above, the present invention relates to a composite material in which Au nanoclusters are supported in a suitable state on a hydrophobic support. The present invention also elucidates a method for supporting Au nanoclusters on a hydrophobic support in an aqueous solvent. According to the present invention, Au nanoclusters can be efficiently supported on a hydrophobic support such as carbon powder.

[0080] The composite material according to the present invention can exhibit a high surface area due to the application of Au nanoclusters and catalytic activity that bulk Au does not have. As a result, the present invention is expected to be used as a catalyst for chemical reactions such as oxidation reactions of carbon monoxide, etc., an electrode catalyst for fuel cells, etc., and an amplifying material for photocatalysts. In addition, the present invention is expected to be applied to various devices that utilize the quantum effect, surface plasmon resonance, optical properties, etc. of Au nanoclusters.

Claims

1. A composite material comprising an Au nanocluster containing two or more Au atoms supported on a particulate support via a ligand, The material of the particulate support is carbon, At least a portion of the particulate support on which the Au nanoclusters are supported is hydrophobic; The particulate carrier has an R SP The value was corrected by the total surface area of ​​the particulate carrier. SP(c) The value of is 0.35 or more and 0.5 or less, The complex wherein the ligand is L-cysteine ​​or an L-cysteine ​​derivative having a non-polar residue.

2. 2. The composite material according to claim 1, wherein the ligand is an L-cysteine ​​derivative having, as the non-polar residue, any one of an acetyl group, an isobutyl group, and a tert-butoxycarbonyl group.

3. A method for producing the composite material according to claim 1 or 2, comprising the steps of: After forming a state in which at least a portion of the particulate support is in contact with an aqueous solvent containing either an Au source or a ligand, adding the other of the Au source and the ligand to the aqueous solvent to synthesize Au nanoclusters in the aqueous solvent and support the Au nanoclusters on the particulate support; A method for producing a composite material, wherein the ligand is L-cysteine ​​or an L-cysteine ​​derivative having a non-polar residue.

Citation Information

Patent Citations

  • Water-soluble graphene-noble-metal nano-composite and preparation method and application thereof

    CN102426868A

  • Method for preparing supported small-granule gold catalyst

    CN107855133A

  • Platinum bimetal electrode catalyst using cysteine as coupling layer and its preparing method

    CN1770523A

  • SELECTIVE LARGE SCALE METHOD FOR PRODUCING Au25 CLUSTER

    JP2007045791A

  • Nanoparticle Production

    JP2019513184A